(untitled) (Journal of Student Affairs in Africa, 2024)
This article delves into the formidable obstacles first-generation students (FGS) encounter within the South African private higher education sector which locates the study on which it is based in the literature around the overall experience of first-generation students. Extensive research has underscored the various challenges faced by FGS, posing hindrances to their academic success in higher education. FGS often grapple with a complex journey fraught with challenges around finances, social adjustment, and epistemological access, to name a few. This research adopts a quantitative approach with a cross-sectional research design. The study utilises a 5-point Likert scale questionnaire supplemented by open-ended questions to gather data from a sample of 1 208 students. The study reveals that close to one-third (30.5%) of the sample found the academic requirements challenging, just less than two-thirds (63.6%) found the coursework overwhelming, and more than half (57.7%) received support from faculty and academic advisors. In terms of financial challenges, less than a quarter (21%) indicated that they face financial challenges most of the time. The results of this study are reflective of similar research on the challenges experienced by South African FGS. The authors suggest that more research is needed to examine the unique challenges the FGS experience at private universities in South Africa. Moreover, the authors argue that an overall systemic and structural transformation is needed to enable institutional changes that would ease the challenges of all students.